International response to the HIV/AIDS epidemic: planning for success - Piot Peter; Coll Seck Awa Marie (The World Health Organization, 2001)
More assertive political leadership in the global response to AIDS in both poor and rich countries culminated in June 2001 at the UN General Assembly Special Session on AIDS. Delegates made important commitments there, and endorsed a global strategy framework for shifting the dynamics of the epidemic by simultaneously reducing risk, vulnerability and impact. This points the way to achievable progress in the fight against HIV/AIDS. Evidence of success in tackling the spread of AIDS comes from diverse programme areas, including work with sex workers and clients, injecting drug users, and young people. It also comes from diverse countries, including India, the Russian Federation, Senegal, Thailand, the United Republic of Tanzania, and Zambia. Their common feature is the combination of focused approaches with attention to the societywide context within which risk occurs. Similarly, building synergies between prevention and care has underpinned success in Brazil and holds great potential for sub-Saharan Africa, where 90% reductions have been achieved in the prices at which antiretroviral drugs are available. Success also involves overcoming stigma, which undermines community action and blocks access to services. Work against stigma and discrimination has been effectively carried out in both health sector and occupational settings. Accompanying attention to the conditions for success against HIV/AIDS is global consensus on the need for additional resources. The detailed estimate of required AIDS spending in low- and middle-income countries is US$ 9.2 billion annually, compared to the $ 2 billion currently spent. Additional spending should be mobilized by the new global fund to fight AIDS, tuberculosis and malaria, but needs to be joined by additional government and private efforts within countries, including from debt relief. Commitment and capacity to scale up HIV prevention and care have never been stronger. The moment must be seized to prevent a global catastrophe.